2004
DOI: 10.1016/j.ab.2004.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of enzymatic degradation of the azo dye Orange II determined by ex situ 1H nuclear magnetic resonance and electrospray ionization-ion trap mass spectrometry

Abstract: Removal of azo dye effluents generated by textile photography industries is a main issue in wastewater treatment. Enzymatic treatment of dyes appears to be one of the most efficient processes for their degradation. The elucidation of degradation pathways is of special interest considering health and environmental priorities. Ex situ nuclear magnetic resonance (NMR) spectroscopy and electrospray ionization (ESI)-ion trap mass spectrometry performed directly on incubation medium have been used for the first time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 38 publications
5
45
2
2
Order By: Relevance
“…All these, generally follow two main routes as proposed by several studies: symmetrical or asymmetrical cleavage of azo bonds. Also few authors suggested co-existence of both the pathways [49]. Based on the identification of intermediates it was obvious that M. vellerea HQ871747 has asymmetrically cleaved RB220.…”
Section: Proposed Mechanismmentioning
confidence: 99%
“…All these, generally follow two main routes as proposed by several studies: symmetrical or asymmetrical cleavage of azo bonds. Also few authors suggested co-existence of both the pathways [49]. Based on the identification of intermediates it was obvious that M. vellerea HQ871747 has asymmetrically cleaved RB220.…”
Section: Proposed Mechanismmentioning
confidence: 99%
“…The identification of the metabolites produced during biodegradation as well as toxicity studies must be done to ensure the safety of the laccase-treated effluents. However, so far only a few studies regarding the metabolic pathway of azo dye degradation by ligninolytic enzymes have been performed (López et al, 2004;Martins et al, 2002Martins et al, , 2003Pereira et al, 2009;Svobodová et al, 2007). The aim of the present work was to determine the biotransformation products resulting from the laccase treatment of the anthraquinonic dye RBBR.…”
Section: Introductionmentioning
confidence: 97%
“…Color is the first contaminant in wastewater, which should be recognized and has to be removed before it can be discharged into the environment (Miao 2005). Physicochemical methods used for color removal of the effluents are effective, but they show disadvantages in terms of operational problems, high cost, and sludge production (Kapdan et al 2000;Ló pez et al 2004;Kodam et al 2005). Moreover, those methods use more energy and chemicals than biological processes (Miao 2005).…”
Section: Introductionmentioning
confidence: 98%